METABOLIC SYNDROME IN FEMALE WORKERS FROM A TEXTILE MILL: EFFECT OF NOISE - SEEMA GUPTA; SUNITA GULATI; Gupta, Gaurav (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Noise creates alteration in human health in both physical as well as psychological variations. Effect of noise on components of metabolic syndrome (MetS) has been discussed but not well established. The aim of this study was to investigate the MetS in female workers from textile mill. Methods: A total of 65 female workers were recruited for the study from the high noise (>70 dB) area and low noise (<40 dB) area of a textile mill. Body mass index (BMI), blood pressure (BP), blood sugar (BS), and lipid profile were investigated of the female workers. BP was estimated by auscultatory method. BS was investigated by glucose oxidase-peroxidase (POD) method. Total cholesterol (TC), triglycerides (TG), high-density lipoprotein cholesterol (HDL-C), and low-density lipoprotein cholesterol (LDL-C) were investigated by cholesterol oxidase (CHOD)-POD method, GPO- PAP method, CHOD-POD/phosphotungustate method, and friedewald formula, respectively. Results: Significant outcomes were obtained in this study. BMI was significantly (<0.01) higher in workers working in high noise area compared to low noise (<40 dB) area. Systolic BP and diastolic BP was also significantly (<0.01) higher in high noise area. Fasting BS level was found to be significantly (<0.01) lower in low noise area. In case of lipid profile significant (<0.01) results were obtained except LDL-C. TC and TG were found to be related with noise since their concentration was higher in high noise area compared to low noise area. However, HDL-C was found to be lower in high noise area compared to low noise area. Conclusion: Continuous exposure to occupational noise might be reason for developing cardiovascular disease depending on the degree of MetS in industrial workers. BP and BS seems to be better predictor of MetS in assessing cardiovascular risk. Keywords: Occupational noise, Metabolic syndrome, Dyslipidemia.